PENGARUH PERSEPSI KEBERMANFAATAN, KEMUDAHAN PENGGUNAAN, DAN RISIKO TERHADAP MINAT MENGGUNAKAN LAYANAN MOBILE BANKING DENGAN ATTITUDE TOWARD USING SEBAGAI VARIABEL INTERVENING (STUDI KASUS MAHASISWA UIN SUMATERA UTARA PENGGUNA BSI MOBILE) - Dhita Lutfiah; Fauzi Arif Lubis; Tuti Anggraini (ITB AAS Indonesia Surakarta, 2024)
With attitude towards usage as an intervening variable, this study intends to determine the link and influence of perceptions of utility, usability, and risk to interest in using mobile banking services. (Study on Mahasiswa in Sumatera Utara Using Bsi Mobile). The study employs an associative quantitative methodology to explain how perceptions of utility, usability, and risk affect interest in utilising mobile banking services, with attitude towards use serving as an intermediary variable. The study is titled